Donor oocyte recipients do not benefit from preimplantation genetic testing for aneuploidy to improve pregnancy outcomes. Issue 11 (15th October 2020) - Doyle, Nicole; Gainty, Michelle; Eubanks, Allison; Doyle, Joseph; Hayes, Heidi; Tucker, Michael; Devine, Kate; DeCherney, Alan; Levy, Michael; Jahandideh, Samad; Hill, Micah
Abstract: STUDY QUESTION: Do donor oocyte recipients benefit from preimplantation genetic testing for aneuploidy (PGT-A)? SUMMARY ANSWER: PGT-A did not improve the likelihood of live birth for recipients of vitrified donor oocytes, but it did avoid embryo transfer in cycles with no euploid embryos. WHAT IS KNOWN ALREADY: Relative to slow freeze, oocyte vitrification has led to increased live birth from cryopreserved oocytes and has led to widespread use of this technology in donor egg IVF programs. However, oocyte cryopreservation has the potential to disrupt the meiotic spindle leading to abnormal segregation of chromosome during meiosis II and ultimately increased aneuploidy in resultant embryos. Therefore, PGT-A might have benefits in vitrified donor egg cycles. In contrast, embryos derived from young donor oocytes are expected to be predominantly euploid, and trophectoderm biopsy may have a negative effect relative to transfer without biopsy. STUDY DESIGN, SIZE, DURATION: This is a paired cohort study analyzing donor oocyte-recipient cycles with or without PGT-A performed from 2012 to 2018 at 47 US IVF centers. PARTICIPANTS/MATERIALS, SETTING, METHODS: Vitrified donor oocyte cycles were analyzed for live birth as the main outcome measure. Outcomes from donors whose oocytes were used by at least two separate recipient couples, one couple using PGT-A (study group) and one using embryos without PGT-A (control group), were compared. Generalized estimating equation models controlled for confounders and nested for individual donors contributing to both PGT-A and non-PGT-A cohorts, enabling a single donor to serve as her own control. MAIN RESULTS AND THE ROLE OF CHANCE: In total, 1291 initiated recipient cycles from 223 donors were analyzed, including 262 cycles with and 1029 without PGT-A. The median aneuploidy rate per recipient was 25%. Forty-three percent of PGT-A cycles had only euploid embryos, whereas only 12.7% of cycles had no euploid embryos. On average 1.09 embryos were transferred in the PGT-A group compared to 1.38 in the group without PGT-A ( P < 0.01). Live birth occurred in 53.8% of cycles with PGT-A versus 55.8% without PGT-A ( P = 0.44). Similar findings persisted in cumulative live birth from per recipient cycle. LIMITATIONS, REASONS FOR CAUTION: Pooled clinical data from 47 IVF clinics introduced PGT-A heterogeneity as genetic testing were performed using different embryology laboratories, PGT-A companies and testing platforms. WIDER IMPLICATIONS OF THE FINDINGS: PGT-A testing in donor oocyte-recipient cycles does not improve the chance for live birth nor decrease the risk for miscarriage in the first transfer cycle but does increase cost and time for the patient. Further studies are required to test if our findings can be applied to the young infertility patient population using autologous oocytes. STUDY FUNDING/COMPETING INTEREST(S): No external funding was used for this study. There are no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.